Strengthening Students' Islamic Character Through the Islamic Personal Development Program: Penguatan Karakter Islami Siswa Melalui Program Bina Pribadi Islami - Parlina, Leni; Martha, Alfroki; Adriantoni, Adriantoni (Universitas Muhammadiyah Sidoarjo, 2025)
The Bina Pribadi Islami (BPI) program at SDIT Almadaniy Lubuk Basung was developed to strengthen students' Islamic character, particularly in the areas of time discipline, self-commitment, and independence. This study aims to evaluate the effectiveness of the BPI implementation as part of Islamic-based character education at the primary education level. The research employed a qualitative descriptive method with data collected through observation, interviews, and documentation. The program assessment was conducted using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings revealed that: (1) program planning was conducted systematically through character goal setting, scheduling, method formulation, and involvement of teachers and parents; (2) implementation included daily worship practices, weekly mentoring, Qur’an memorization and recitation, and character-building through daily student interactions; (3) evaluation was carried out through direct observation, monitoring books, and regular reflection sessions; and (4) the program's effectiveness was evident in students’ increased time discipline, personal commitment, and independence. This study also contributes to the development of a contextual and integrated Islamic character education model. Highlights: Structured Planning: The BPI program was systematically planned with defined goals and teacher-parent collaboration. Holistic Implementation: Activities included worship routines, Qur’an memorization, and character-based interactions. Positive Impact: Students showed noticeable improvements in discipline, commitment, and independence. Keywords: Islamic Character Education, Time Discipline, Self-Commitment, Primary Education, Program Evaluation